ON THE BEHAVIORAL ASSESSMENT OF SEMANTICS. - KRANTZ, KYLE (ETC: A Review of General Semantics, 2016)
The article explores the role of behaviorism in the assessment of computational semantics. Topics discussed include Intelligent Quotient (IQ) measures tend to roughly measure the processing speed, several personality traits tend to account for large life outcomes and fail miserably to assess degrees of raw semantics, and mechanism of the distinction of self-consciousness and being emergence out of sense perception.